Pengaruh Media Audiovisual pada Model Problem Based Learning (PBL) terhadap Hasil Belajar Peserta Didik Kelas XII MIA SMA Negeri 2 Makassar (Studi pada Materi Pokok Reaksi Redoks dan Sel Elektrokimia) - Damayanti, Risdah; Muharram, Muharram; Auliah, Army (ChemEdu, 2021)
This study aims to know the influence of audiovisual media in PBL model towards learning outcomes of XII MIA students SMA Negeri 2 Makassar on subject matter redox reaction and electrochemistry cell. Pretest-posttest control group design was used for all of XII MIA class SMA Negeri 2 Makassar with a total of 351 students as the study population. The study sample that was determined randomly are XII MIA3 as experimental class was taught through PBL model with audiovisual media and XII MIA4 as control class was taught without audiovisual media on PBL model, while as a dependent variable is learning outcomes of students. Non-parametric test (Mann-Whitney test) used on data that are not normally distributed with ∝=0.05 and dk=1.64 was done with Zcalculated > Ztable (4,659>1,64) which means that H0 unaccepted and H1 accepted, it can be concluded there is influence of audiovisual media in PBL model towards learning outcomes of XII MIA students SMA Negeri 2 Makassar on subject matter redox reaction and electrochemistry cell.